Features of refrigeration screw compressor operation at ambient temperature decrease - A. N. Noskov; M. Shaposhnikova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
With a decrease in ambient temperature, the heat gain on the refrigeration machine and condensation pressure decrease, which requires a decrease in cooling capacity and geometric compression ratio of the screw compressor. A condensation pressure decrease below a certain value disrupts the stable operation of throttling devices. The article describes the operation scheme of the refrigeration machine with a screw compressor and a liquid pump before the throttling devices, which allows it to work at a decreased condensation pressure. The dependences of changes in net efficiency, cooling capacity, power consumption and cooling coefficient at full and partial capacity with co-regulation of cooling capacity and geometric compression ratio are given. The experimental and calculated characteristics of a screw compressor operating with R22 freon are used